A Structural Model of Health-Related Quality of Life in Parkinson's Disease Patients. (August 2015) - Lee, JuHee; Choi, MoonKi; Jung, Dukyoo; Sohn, Young H.; Hong, JinYong
Disability-adjusted life expectancy is focused on more than just extending life span; thus, health-related quality of life (HRQOL) has emerged as an important issue for elderly patients with chronic disease. The number of patients with Parkinson's disease (PD) is predicted to grow along with the aging population, so it is essential to identify the predictors of HRQOL. This study utilized structural equation modeling (SEM) to predict the HRQOL of patients with PD. Participants ( N = 217) were patients diagnosed with PD ( M age = 66.01). Demographic and disease-related characteristics, sleep quality, pain, depression, and HRQOL were investigated via a structured questionnaire. Participants' functional factors were measured using physical function evaluations. The hypothetical model verified disease-related factors, depression, and pain as direct factors that significantly predicted HRQOL of patients with PD (Goodness of Fit Index = 0.93 and Comparative Fit Index = 0.96). These findings are useful for developing comprehensive interventions to improve the HRQOL of patients with PD.